Forgotten Variants (Hor. Carm. 1. 6. 7; 1. 9. 8; 1. 7. 7) - Egorova, Sofia (Hyperboreus, 2020)
In the article three variants for the text of Horace’s odes are reconsidered, as they were omitted from editions, unnecessarily in my opinion. In the ﬁrst case (Carm. 1. 6. 7) duplices (vs. duplicis) is represented in a large number of reliable manuscripts, though it is not considered principal because of both ancient commentaries mentioning the ambiguity “duplicis Ulixei – duplicis cursus”. Meanwhile the adjective duplicis, duplices or dupliceis as referring to the noun cursus suits the main topic of the ode better – Horace rejects epic subjects, one of them being the redoubled journey of Odysseus, i.e. twice longer than that of other Greek heroes. The second variant – Sabino diota in place of the usual Sabina diota (Carm. 1. 9. 8) – was found only in two manuscripts, and thus the editors chose the variant for publication taking into account the majority of mss. I also consider this rare Greek word to mean the same as the Graeca testa (Carm. 1. 20. 2 according to the interpretation of Nisbet and Hubbard), a vessel impregnated with salt, used for conserving. The third variant in Carm. 1. 7. 7 is not represented in manuscripts and is a part of a conjecture by Erasmus (he proposed decerptae frondi in the place of decerptam fronti). The existing text contains the phrase fronti praeponere olivam which has no parallel for the meaning ‘to place in front’. Meanwhile a more common meaning ‘to prefer’ with the Dative frondi could be understood as “to prefer an olive even picked elsewhere to <any other> foliage”.